Autonomic Dysfunction in Wilson's Disease: A Comprehensive Evaluation during a 3-Year Follow Up - Li, Kai; Lindauer, Charlotte; Haase, Rocco; Rüdiger, Heinz; Reichmann, Heinz; Reuner, Ulrike; Ziemssen, Tjalf (Frontiers in Physiology, 2017)
Objectives Wilson’s disease is reported to have autonomic dysfunction, but comprehensive evaluation of autonomic function is lacking. Additionally, little is known about the change of autonomic function of Wilson’s disease during continuous therapy. We assumed that patients with Wilson’s disease had both sympathetic and parasympathetic autonomic impairments, and the autonomic dysfunction might be stable across a three-year follow-up after years of optimal treatment. Methods Twenty-six patients with Wilson’s disease and twenty-six healthy controls were recruited. Twenty patients in the Wilson’s disease group were examined again after a three-year follow-up. All the participants were evaluated by a questionnaire on dysautonomia symptoms, 24-hour blood pressure and heart rate monitoring, and cardiovascular autonomic function examination in various conditions including at rest, deep breathing, Valsalva manoeuvre, isometric handgrip test and passive tilting. Baroreflex sensitivity and spectral analyses were performed via trigonometric regressive spectral analysis. Results Patients with Wilson’s disease showed autonomic dysfunction mainly in the following aspects: 1.the heart rate was higher than the controls. 2. Valsalva ratio was lower in patients with Wilson’s disease compared with the controls. 3. Heart rate increase during isometric hand gripping was smaller in the Wilson’s disease patients than the controls. 4. Baroreflex sensitivity was lower during nearly all the cardiovascular autonomic function examinations compared with healthy controls. When tested three years later, baroreflex sensitivity at rest decreased compared with baseline. 5. There were mild declines of resting DBP and low frequency component of heart rate variability during the follow-up examination compared with baseline. 6. Subgroup analysis showed that patients initially presenting with neurological symptoms had a higher night-time heart rate, lower expiration: inspiration RR interval ratio (E/I ratio), lower expiration: inspiration RR interval difference (E-I difference), less increase of heart rate and diastolic blood pressure during the handgrip test, and lower baroreflex sensitivity during deep breathing than the control group. 6. Correlation analysis showed that the severity of neurological symptoms was associated with E/I ratio, E-I difference, Valsalva ratio, heart rate change during the handgrip test, and baroreflex sensitivity during deep breathing. Conclusions The present study reveals cardiovascular autonomic dysfunction involving both sympathetic and parasympathetic branches in